The Offensiveness of the Freedom to Begin.: Feminist Critique – Feminism Critique - Thürmer-Rohr, Christina (HannahArendt.net, 2022)
Christina Thürmer-Rohr begins by criticising Arendt's conception of public space as an “elitist project” in which competition and fame dominate. This idea of the public sphere would structurally exclude women, as bell hooks and Seyla Benhabib, among others, emphasise. Thürmer-Rohr, however, contradicts the feminist critique of Arendt: “Thinking with Arendt does not lead away from a feminist critique of domination, but deepens it by breaking profoundly with the hegemonic concept of identity that destroys political space by destroying plurality.”